DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA ON CLASS X PAYMENT SYSTEMS AND TOOLS MATERIALS AT SMAN PAKUSARI - Febriyanti, Cindy; Sukidin, Sukidin; Tiara, Tiara (Journal of Economics Education and Entrepreneurship, 2025)
The aim of this research is to create interesting and effective Android-based interactive learning media that focuses on system material and payment tools for class X at SMAN Pakusari. For this research, the ADDIE Dick&Carey development model was used, which consists of the steps of analysis, design, development, implementation and evaluation. Material, language and design expert validation is carried out to test feasibility. The trial consisted of two groups: a limited group consisting of 12 students from class X-1 and a wide group consisting of 36 students from class X-8. Tests, questionnaires, interviews, and validation sheets are some of the data collection tools used. Tests of attractiveness and effectiveness are the data analysis methods used. Using descriptive analysis, test the level of product attractiveness. In addition, the Paired Sample T-test is used to evaluate product effectiveness. The limited group had an attractiveness rate of 85.33%, which is considered very attractive, and the broad group had an attractiveness rate of 90.11%. With a significance value of <0.05, the findings of this development research indicate that Android-based interactive learning media is more effective and interesting than previous media. The results show that the pretest and posttest results before and after using this media are very significant.